Early Development of the Threespine Stickleback in Relation to Water pH - Glippa, Olivier; Brutemark, Andreas; Johnson, Justin; Spilling, Kristian; Candolin, Ulrika; Engström-Öst, Jonna (Frontiers in Marine Science, 2017)
Ocean acidification is a growing environmental problem, and there is a need to investigate how the decreasing pH will affect marine organisms. Here we studied the effects of lowered pH on the growth and development of the threespine stickleback (Gasterosteus aculeatus) eggs. Adult fish, collected from the natural environment, were allowed to mate in aquaria and the newly produced eggs were incubated in an experiment. Eggs and larvae from ambient conditions (produced in the laboratory) were reared at three different pH concentrations (control: pH 7.8; and reduced pH treatments: pH 7.5 and 7.0) for 21 days in the laboratory. Dissolved oxygen concentration (8.1 ± 0.1 mg l-1) and temperature (18.6 ± 0.02°C) were monitored regularly. Then, egg diameter, larval length, weight and survival were measured. There was no relationship between egg diameter and pH or oxygen, but a negative relationship was found with temperature. Survival of larvae was not affected by pH or temperature, whereas dissolved oxygen concentration had a positive effect on number of survivors. The pH did not have a significant effect on the final larval length on day 21, but interacted significantly with dissolved oxygen. Higher temperatures were found to have a positive effect on the final larval length and weight. Larval weight, on the other hand, was not related to pH nor oxygen. Coastal zones are characterized by pH levels that fluctuate due to natural processes, such as upwelling and river runoff. Our results suggest that the threespine stickleback larvae are well adapted to the different pHs tested, and egg development will likely not be affected by decreasing pH, but even slight temperature and oxygen changes can have a great impact on the threespine stickleback development.